STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN LEMBAGA PENDIDIKAN YANG UNGGUL DI PAUD AL-MUNAWAROH PAMEKASAN - Norhayati, Siti; Usman, Jamiludin (re-JIEM (Research Journal of Islamic Education Management), 2021)
The main discussion in this study is the strategy of the PAUD head in realizing superior PAUD, the social capital owned by the school, and the inhibiting factors for the principal in realizing superior PAUD in PAUD Al-Munawwarah Pamekasan. This research uses a case study design with a qualitative approach. The results of the study indicate that the principal's strategy in realizing superior PAUD is that a principal must have a clear vision and mission, and a principal is friendly to teachers, parents, and also to students. In addition, a school principal must provide a good service to his guests. Institutions must have social capital by establishing a good relationship with the community around the institution or the outside community and collaborating with several agencies, as well as providing a good service to guests. The inhibiting factor is from the personal head who must know the character of all teachers and must also balance the guardians of students well, and the guardians of students do not agree with the school program.